Histological assessment of blood cockles (Anadara granosa) using different stains and fixatives. - Nasruddin, Nurrul Shaqinah; Mohd Daud, Hassan; Matori, Mohd Fuad (2010)
Blood cockles (Anadara granosa) or locally known as ‘kerang’ are mollusc belonging to Bivalvia class. It is an important fisheries commodity and a delicacy in Malaysia. In RMK-9, one of the objectives of Malaysia’s aquaculture industries is to maximize the production of bivalves up to 130,000 MT per year, which includes cockles, green mussels, clams and oysters. Cockles become one of the important bivalves cultured in Malaysia as it had very good market value in Malaysia, Thailand and Singapore. According to Phillips and Muttarasin (1985), 80% of the cockles marketed in Thailand were imported from Malaysia. In spite of the diversity and its economic importance, the knowledge of bivalves specifically cockle medicine should be developed in order to meet the requirement of diagnostic work which is necessary in determining the cause of diseases infecting the animals. Up to date, there is no comprehensive information of the histology of cockles. Thus, this study was undertaken to provide basic histological descriptions of normal and anomalies microstructures in Anadara granosa by using different fixatures and stains. Forty live cockles were divided into two groups; one group was fixed with Davidson solution and the other fixed with 10% buffered formalin. The tissues were then processed for 18 hours, and later embedded with paraffin wax and sectioned at 5 µm thickness. There were stained with four stains namely, Haematoxylin and Eosin, Masson’s Trichome, Periodic Acid Schiff’s and Van Gieson’s stains. The sections were evaluated under a computer attached-compound light microscope at low and high magnification. The organs were assessed for microscopic structures staining affinity (Cox et al., 2006). Haematoxylin and Eosin stain was considered the better stain to be used for mantle, foot complex and haemocytes tissues. Combination of Haematoxylin and Eosin and Periodic Acid Schiff’s stains can be used to stain digestive system and palp. Gills could be stained with Masson’s Trichome and Van Gieson’s, while for gonads Masson’s Trichome would be the preferred choice. Van Gieson’s on the other hand, was the choice for foreign body detection. Gills of cockles could be divided into three parts: frontal, intermediate and abfrontal zone similar to Mytella falcate (David et al., 2008). The intermediate zone have a homogenous densely stained structure embedded in the filament which highly indicative that it provided supportive frame to the frontal zone.